디지털 시대의 매개적 신체와 조형예술의 융합 - 패션과 결합한 신체의 확장 개념을 중심으로 - 김정지; Jung Ji Kim (한국디자인포럼, 2018)
연구배경 현대사회에 이르러 장르의 경계가 무너지고 많은 부분이 상호 간섭을 하게 됨에 따라 기존의 형이상학적인 사유에서 벗어나 인간의 실천적 삶을 행하는 직접적 수단으로 신체를 재조명하고 있다. 최근 예술과 패션, 건축 그리고 기술과 결합하여 인간의 신체를 통한 융합으로 문화적인 코드를 생성하고 있는 구체적인 예를 고찰하고 그 현황에 대한 분석을 통해 새로운 현대 예술 조형의 가능성을 제시하고자 한다. 연구방법 인간의 신체에 대한 인식의 변화와 이에 따른 예술적 재현의 문제를 다루고 있기에 신체와 건축, 문화, 패션 등의 관계에 대한 역사적인 고찰이 선행된다. 특히 맥루언의 ‘미디어 확장론’에 근거하여 디지털 기술의 발달로 신체와 환경, 신체와 기계적인 결합 사이의 경계가 허물어지는 가운데 21세기의 예술이 분야 간의 통합으로 구축되어 공감각적 경험을 유도하는 최신 경향을 살펴본다. 연구결과 시각중심주의를 벗어나 공감각적 경험 중심의 실행 방식으로 변경되고 있는 현대미술의 역사적인 배경을 고찰하고 전통적인 예술 형식 분류의 경계를 해체하는 패션과 예술, 그리고 건축과 기술의 혼성적인 융합작품을 보여주는 현시점 작가들의 사례를 조사하였다. 신체의 운동성과 속도 및 움직임을 탐지하고 가속화 시킬 수 있는 유연한 직물적인 특성의 외피를 통한 구축은 인간의 행위와 주변의 상황에 대해 상호 작용하는 반응체로서 주변을 통합시키는 가능성을 내포하게 된다. 결론 미래의 실루엣의 의미가 단순히 신체의 윤곽선을 나타내는 것이 아니라 정신적인 내부와 공간적인 외부가 교류하는 소위 인터페이스(interface)의 경계의 역할을 할 것이라는 것에 주목하며 이러한 역동적인 변혁은 가속화 되리라고 예견된다. Background Recent most outstanding phenomenon in modern society has been the convergence of traditional genres. The human body is reexamined as a direct means to live practical life which is developing from existing metaphysical thinking. I would like to present the possibility of a new contemporary art formative through the analysis of the present situation through fusion of art, fashion, architecture, and technology, through the mediated human body. Methods Since it deals with the change of the perception of human body and the artistic reproduction of it, historical review of the relationship between body, architecture, culture, and fashion is to be preceded. In this paper, firstly I examine the historical background of contemporary art, which is changing from the visual perception to the multisensory experience. execution method. In addition, I investigated the current artists who showed hybrid conversion of fashion, art, architecture and technology to deconstruct the boundaries of classical art forms. Result Marshall McLuhan has described a change in the relationship between the human being and the environment through media in the concept of "extended body." Recent developments in digital technology and media have shown the possibility that human body can be combined with a medium to become the subject of sense and action. Therefore, the limits of traditional human perception experience are constantly reevaluated and expanded, and research focusing more actively on the human environment. Including virtual space is deepening and focusing on the flexible body concept that is transformed accordingly. Conclusion Paying close attention to the meaning of that future silhouette is not merely an outline of the body, but that it will serve as the boundary of the so-called interface between human spirit and outer space, dynamic transformation is expected to accelerate.